THE CONCEPT AND TYPES OF PRINCIPLES OF LEGAL LIABILITY (Law and Safety, 2018)
It has been established that the principles of legal liability are the main guiding ideas that characterize the nature and purpose of legal liability, determine the procedure of its laying and fixed in formal sources, constitution, laws and international treaties.It has been proved that depending on the scope of the principles of legal liability within the system of law one should isolate general legal, intersectorial principles of legal liability.General legal principles of legal liability are common to all types (forms) of this legal phenomenon, regardless of the specifics of method and the subject of legal regulation of a particular field of law. These include the principles of legality, reasonableness, fairness, feasibility, inevitability, timeliness.Intersectorial principles of legal liability are starting, guiding principles of several related fields of law, characterizing the nature and purpose of legal liability, determine the procedure of its laying and fixed in regulatory acts that are sources of related areas of law. Examples of intersectorial principles of legal liability are the principle of responsibility for the guilt, the principle of responsibility without guilt.Sectoral principles of legal liability are basic (guiding) principles, which characterize the nature and purpose of a particular (sectoral) type of legal liability, determine the procedure of its laying and fixed in the sources of law of a particular field of law.